Pathogenic Leptospira isolated from rodents in New Orleans, Louisiana USA, and associated site information ... - Peterson, Anna; Blum, Michael; Ghersi, Bruno; Riegel, Claudia; Wunder, Elsio; Childs, James (Dryad, 2020)
Land use change can elevate disease risk by creating conditions beneficial to species that carry zoonotic pathogens. Observations of concordant global trends in pathogen prevalence and disease incidence have engendered concerns that urbanization could increase transmission risk of some pathogens. Yet host-pathogen relationships underlying transmission risk have not been well characterized within cities, even where contact between humans and species capable of transmitting pathogens of concern occur. We addressed this deficit by testing the hypothesis that areas in cities experiencing greater population loss and infrastructure decline (i.e., counter-urbanization) can support a greater diversity of host species and a larger and more diverse pool of pathogens. We did so by characterizing pathogenic Leptospira infection relative to rodent host richness and abundance across a mosaic of abandonment in post-Katrina New Orleans (Louisiana, USA). We found that Leptospira infection loads were highest in areas that ... : All animals were collected in the field using live trapping as also outlined in https://doi.org/10.1016/j.landurbplan.2019.103710. Tissue samples were collected immediately at necropsy and frozen at -80C. To identify pathogenic Leptospira to species, we sequenced a partial region of the glmU gene using genomic kidney DNA from all individuals that tested positive for Leptospira infection in the qPCR screen. After PCR amplification following a standard protocol, we cleaned all PCR products with ExoSAP-IT (Affymetrix, Santa Clara, CA, USA) and completed final paired sequencing reactions consisting of 3.75 µL PCR grade H20, 3.75 µL 5uM MgCl2, 1.0 µL each of 10 mM forward and reverse glmU primers (respectively) and 0.5 µL BigDye terminator (Applied Biosystems, Foster, CA, USA). We cleaned reactions using Sephadex columns prior to electrophoresis on an ABI 3730xl (Applied Biosystems). We aligned trimmed sequences with GenBank archived sequences of the glmU gene for all pathogenic Leptospira. We then constructed ...